PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF TRAINING TEACHERS TO WORK WITH GIFTED STUDENTS: IMPROVING EDUCATIONAL STRATEGIES FOR PEOPLE WITH EXCEPTIONAL THINKING - Yuldoshev , Bobir (Educational Research in Universal Sciences, 2024)
This article examines the psychological and pedagogical aspects of effectively preparing teachers to work with gifted students. The characteristics and needs of gifted students are discussed, emphasizing the importance of understanding their unique psychological profile to provide appropriate educational opportunities. In addition, the article examines the role of teachers in nurturing and developing the potential of gifted students, emphasizing the need for specialized training and ongoing professional development. Explores a variety of theoretical frameworks and instructional strategies that support the education of gifted students, with a focus on promoting cognitive and social-emotional development. The article concludes by emphasizing the critical role of the teacher-student relationship and the importance of creating a supportive and inclusive learning environment for gifted students.